2011
DOI: 10.14707/ajbr.110011
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Internet Buying Behavior in India

Abstract: Internet penetration in India has become more widespread on account of easy payment options, reduced hardware prices, faster and cost effective internet communication, and reliable technology. Internet applications such as emailing, e-banking, e-gaming, travel and entertainment bookings have become part and parcel of the growing tech-savvy population in India. Although new business models focusing on e-retailing are providing exciting services to satisfy e-consumers' demands, the Indian internet retail market … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Both factors classify the target consumer segment of this study. Also, higher income and higher positions were associated with more awareness of technology and more purchasing power (Nayyar & Gupta, 2011). The level of income implies having the privilege of shopping while education level and PC literate factors qualifies the ability to use online shops.…”
Section: Previous Research and Casesmentioning
confidence: 96%
See 3 more Smart Citations
“…Both factors classify the target consumer segment of this study. Also, higher income and higher positions were associated with more awareness of technology and more purchasing power (Nayyar & Gupta, 2011). The level of income implies having the privilege of shopping while education level and PC literate factors qualifies the ability to use online shops.…”
Section: Previous Research and Casesmentioning
confidence: 96%
“…Online shopping framework by Vazquez & Xu (2008) In figure 13, Nayyar & Gupta (2011) studied the following variables, Demography, perceived usefulness, perceived ease of use, perceived risk as determinants of internet buying behavior. Given the demographics, it was found that the gender differences have an effect; "The findings of this study have revealed a higher number of male internet shoppers than females" (Nayyar & Gupta, 2011). In addition to the introduction of a new parameter to classify and segment the consumers as PC literate and illiterate, therefore, the PC illiterate are out of scope of this study.…”
Section: Previous Research and Casesmentioning
confidence: 99%
See 2 more Smart Citations
“…This study has several managerial implications. In recent times, researchers have tried to explore the different dimensions of online marketing relating to Indian context (Mahapatra & Sreekumar, 2012;Nayyar & Gupta, 2011;Sahney, Ghosh & Shrivastava, 2013;Thamizhvanan & Xavier, 2013) but they have restricted their study within the economic value and functional advantages. There have been no such empirical evidences that can portray process in knowing how the Online Retail Brand Engagement can be strategically created to support the Final Brand Selection and Purchase Intention of the potential customer at Indian online marketplace.…”
Section: Conclusion and Managerial Implicationsmentioning
confidence: 99%